The Effect Of Lower Rom Active On The Risk Of Falls In The Elderly - Fanny Dewi Sartika (Jurnal EduHealth, 2023)
A fall is an event in which a person accidentally falls sitting on the ground or in a lower place To determine the effect of active lower joint range of motion exercises on the risk of falls in the elderly. This research is research using the Quasy experimental design method with a cross sectional approach with Purposive Sampling technique. Elderly people at risk of falls discerning using the TUG test. Examination of the risk of falls using the TUG test were carried out pre and post. The results of the study showed that there was an effect of lower joint range of motion training on the risk of falls in the elderly with a p value <0.05. and than conclusion Lower ROM has benefits in reducing the risk of falls in the elderly